Incidence of Sturge–Weber syndrome and associated ocular involvement in Olmsted County, Minnesota, United States. (3rd March 2020) - Rihani, Heba T.; Dalvin, Lauren A.; Hodge, David O.; Pulido, Jose S.
ABSTRACT: Background : Sturge–Weber syndrome (SWS) is a rare sporadic syndrome characterized by nevus flammeus (port-wine stain, PWS) in the trigeminal nerve distribution, diffuse choroidal hemangioma, and brain leptomeningeal hemangioma. We are unaware of previous reports of SWS incidence in the United States. This study investigated SWS incidence and associated ocular involvement in Olmsted County, Minnesota. Materials and methods : The Rochester Epidemiology Project database was used to identify SWS cases from January 1, 2000–December 31, 2017. Incidence of SWS was calculated using the Olmsted County census population. A literature review of studies investigating SWS-associated ocular involvement was also performed. Results : There were 13 patients with SWS in Olmsted County classified as type 1 (31%) or type 2 (69%). Age and sex-adjusted incidence of SWS was 0.19/100, 000/year. Race was predominantly Caucasian (85%), with sex female (69%) or male (31%). All patients had PWS, mostly with unilateral distribution in the V1 and/or V2 region (85%). Two cases (15%) had associated Klippel–Trenaunay syndrome. The most common ocular features included: dilated episcleral vessels (46%), glaucoma (46%), retinal detachment (23%), DCH (7.7%), strabismus (31%), and refractive error (38%). PWS in the V1 distribution was associated with all cases of glaucoma, DCH, and neurological involvement. Severe visual impairment (>0.6 LogMAR, Snellen equivalent ≤20/100) was found in (23%) at final follow-up, and one patient (8%) required enucleation for uncontrolled glaucoma. Conclusions : SWS affects approximately 0.19/100, 000/year in Olmsted County. Early diagnosis, intervention, lifelong follow-up, and multidisciplinary approach should be used to optimize systemic and ocular outcomes.